Autologous CD34+ cell therapy improves exercise capacity, angina frequency and reduces mortality in no-option refractory angina: a patient-level pooled analysis of randomized double-blinded trials. (5th January 2018) - Henry, Timothy D; Losordo, Douglas W; Traverse, Jay H; Schatz, Richard A; Jolicoeur, E Marc; Schaer, Gary L; Clare, Robert; Chiswell, Karen; White, Christopher J; Fortuin, F David; Kereiakes, Dean J; Zeiher, Andreas M; et al.
Abstract: Aims: Autologous CD34 + (auto-CD34 + ) cells represent an attractive option for the treatment of refractory angina. Three double-blinded randomized trials ( n = 304) compared intramyocardial (IM) auto-CD34 + cells with IM placebo injections to affect total exercise time (TET), angina frequency (AF), and major adverse cardiac events (MACE). Patient-level data were pooled from the Phase I, Phase II ACT-34, ACT-34 extension, and Phase III RENEW trials to determine the efficacy and safety of auto-CD34 + cells. Methods and results: Treatment effects for TET were analysed using an analysis of covariance mixed-effects model and for AF using Poisson regression in a log linear model with repeated measures. The Kaplan–Meier rate estimates for MACE were compared using the log-rank test. Autologous CD34 + cell therapy improved TET by 46.6 s [3 months, 95% confidence interval (CI) 13.0 s–80.3 s; P = 0.007], 49.5 s (6 months, 95% CI 9.3–89.7; P = 0.016), and 44.7 s (12 months, 95% CI − 2.7 s–92.1 s; P = 0.065). The relative frequency of angina was 0.78 (95% CI 0.63–0.98; P = 0.032), 0.66 (0.48–0.91; P = 0.012), and 0.58 (0.38–0.88; P = 0.011) at 3-, 6- and 12-months in auto-CD34 + compared with placebo patients. Results remained concordant when analysed by treatment received and when confined to the Phase III dose of 1 × 10 5 cells/kg. Autologous CD34 + cell therapy significantly decreased mortality (12.1% vs. 2.5%; P = 0.0025) and numerically reduced MACE (38.9% vs. 30.0; P = 0.14) at 24 months. Conclusion: Treatment with auto-CD34 + cells resulted in clinically meaningful durable improvements in TET and AF at 3-, 6- and 12-months, as well as a reduction in 24-month mortality in this patient-level meta-analysis.